Digital instrument for diameter forest measurement using low-cost microcontroller (Research, Society and Development, 2021)
This study tests the process of creating and assembling a system for automated data acquisition of diameter at breast height. The construction of the mobile prototype included the following components: Arduino Pro mine, Micro SD Card Module, Distance Sensor, LCD Display and Joystick Module. The system was assembled in a transparent plastic pool. Data validation was performed by comparing the diameter at breast height values ​​collected with the conventional bra and the built prototype, through frontal and lateral measurements of a Eucalyptus grandis plantation. The results showed a positive correlation between the data obtained by the conventional method, using a mechanical brace, and the data obtained from the prototype made. Pearson's correlation coefficient was 0.92 and 0.91 for frontal and lateral measurements, respectively. The project proves to be viable for use within the forestry sector, mainly due to the low cost of production. However, the presented prototype needs further adjustments, especially in its structure, in order to facilitate handling.